Return to Armageddon : the United States and the nuclear arms race, 1981-1999 - Powaski, Ronald E. (Oxford University Press, 2000)
During the Reagan, Bush and Clinton administrations, the United States, through its victory in the Cold War, led the world away from the brink of nuclear annihilation, and then slowly became aware of the increased threat of nuclear confrontation in a world more splintered than ever before.